Genome-wide identification and characterization of ADH gene family and the expression under different abiotic stresses in tomato (Solanum lycopersicum L.) - Zhu, Qingdong; Han, Yading; Yang, Wentao; Zhu, Hang; Li, Guangtong; Xu, Ke; Long, Mingxin (Frontiers in Genetics, 2023)
The SlADH gene plays a key role in environmental stress response. However, limited studies exist regarding the tomato SlADH gene. In this study, we identified 35 SlADH genes in tomato by genome-wide identification. Among the 12 chromosomes of tomato, SlADH gene is distributed on 10 chromosomes, among which the 7th and 10th chromosomes have no family members, while the 11th chromosome has the most members with 8 family members. Members of this gene family are characterized by long coding sequences, few amino acids, and introns that make up a large proportion of the genetic structure of most members of this family. Moreover, the molecular weight of the proteins of the family members was similar, and the basic proteins were mostly, and the overall distribution was relatively close to neutral (pI=7). This may indicate that proteins in this family have a more conserved function. In addition, a total of four classes of cis-acting elements were detected in all 35 SlADH promoter regions, most of which were associated with biotic and abiotic stresses. The results indicate that SlADH gene had a certain response to cold stress, salt stress, ABA treatment and PEG stress. This study provides a new candidate gene for improving tomato stress resistance.